OBESITY AND SOCIAL INEQUALITIES: HOW SOCIOECONOMIC FACTORS AFFECT HEALTH - Karolina Witek; Marta Nowocień; Anna Mandecka; Kornela Kotucha-Cyl; Weronika Komala; Natalia Guzik; Joanna Gerlach; Dorota Plechawska; Joanna Kaźmierczak (International Journal of Innovative Technologies in Social Science, 2025)
Background: Obesity represents one of the greatest public health challenges of the 21st century. Its prevalence is strongly linked to socioeconomic factors rather than being solely the result of individual dietary choices or lifestyle behaviors. According to the World Health Organization (WHO), obesity is a consequence of excessive fat accumulation leading to metabolic disorders, an increased risk of cardiovascular diseases, type 2 diabetes, and premature mortality. Over the past decades, the global prevalence of obesity has risen dramatically, increasingly affecting individuals with lower socioeconomic status. This highlights the need to analyze the social determinants underlying this phenomenon. Objective: The aim of this paper was to present and analyze the current state of knowledge regarding the impact of socioeconomic factors, such as education level, income, place of residence, and access to healthcare, on the prevalence of obesity, as well as to discuss their health and social consequences. Methods: A literature review was conducted using scientific databases including PubMed and Google Scholar, as well as reports from international organizations such as the World Health Organization (WHO) and the Organisation for Economic Co-operation and Development (OECD). The search focused on recent publications examining the relationship between socioeconomic status and obesity. The review included original studies, review papers, and reports analyzing the effects of education, income, place of residence, and healthcare accessibility on obesity risk and its health outcomes. Results: The analysis revealed that individuals with lower socioeconomic status are significantly more likely to suffer from overweight and obesity. Contributing factors include limited access to healthy foods, infrastructure that promotes physical activity, preventive healthcare, and health education. Residents of areas with lower socioeconomic development are more exposed to phenomena such as “food deserts” and “food swamps,” which promote unhealthy eating habits. Furthermore, people living with obesity often experience stigma and discrimination, leading to reduced quality of life and lower treatment effectiveness. Conclusions: Obesity is not only a medical issue but also a social one, deeply rooted in socioeconomic structures. Effective prevention requires an integrated, systemic approach that combines actions in education, health policy, and urban planning. Key measures include improving access to healthy food, developing infrastructure that supports physical activity, enhancing the quality of healthcare, and reducing economic barriers. Reducing social inequalities can significantly contribute to lowering the prevalence of obesity and its long-term health consequences.